Determining Point of Burst of Artillery Shells using Acoustic Source Localisation - Sreeramamurthy, Vanapalli; Dutta, Saptarsi; Padhy, Sankarsan; Bose, Aniruddha (Defence Science Journal, 2015)
Source localisation is a method to estimate position of a source. In case of acoustic source localisation (ASL), the location of sound source is estimated using acoustic sensors such as a microphone. In case of ASL, time difference of arrival (TDOA) from each pair of microphones is estimated. For any pair of microphones, the surface on which the TDOA is constant is a hyperboloid of two sheets. Then the source location is estimated at the point where all associated hyperboloids most nearly intersect. This concept has been used in our range in finding the point-of-burst of artillery shell using an array of sensors. In this paper, a simulation model has been developed to examine the applicability of acoustic source localisation for determining point-of-burst of artillery shells. The randomness in the model has been incorporated in terms of gustiness of downrange sea wind. The result of the simulation has been validated with trajectory data of projectiles tracked by radar. Finally, an acoustic sensor array-based setup has been developed and used for localising point-of-bursts. Science Journal, Vol. 64, No. 6, November 2014, pp.517-523, DOI:http://dx.doi.org/10.14429/dsj.64.8112